Impact of Contextual Factors on the Perceived Participation of People With Multiple Sclerosis and Gait Impairment Using Mobility Assistive Devices: A Qualitative Analysis - Elise‐Marie Dilger; Nadja Reeck; Dyon Hoekstra; Annett Thiele; Anna Levke Brütt (Wiley, 2024)
ABSTRACT Introduction People with multiple sclerosis and gait impairment are particularly susceptible to facing restrictions in their participation. This study aims to investigate (a) which contextual factors within the framework of the International Classification of Functioning, Disability and Health (ICF) are relevant for participation from the perspective of people with multiple sclerosis and gait impairment who (intend to) use mobility assistive devices, and (b) how these contextual factors shape the subjective facets of participation, including a sense of connection, efficacy and meaning, based on the social identity approach to health and well‐being. Methods We conducted a qualitative analysis on data gathered from four online focus group interviews, each involving four to six people with multiple sclerosis and gait impairment who (intend to) use mobility assistive devices (totalling N = 19), and 12 individual online interviews conducted with participants from the focus group interviews. The analysis followed the qualitative content analysis according to Kuckartz. Results Mobility assistive devices such as walkers, manual wheelchairs and electric wheelchairs/scooters were seen as facilitators that enabled participation in various life situations and enhanced a sense of efficacy by promoting independence. Challenges were encountered in relation to architectural barriers, pathways, weather conditions, public transportation and the lack of integral accessibility to services and systems. Although instrumental support could ease participation, it was also associated with an impaired sense of efficacy. Attitudes, particularly developing an understanding of the experiences of people with multiple sclerosis and gait impairment from others' perspectives, were considered important but often lacking, and discriminatory attitudes were experienced. On the level of personal factors, acceptance of both the mobility assistive devices and the disease itself were seen as facilitators for maintaining involvement in life situations. Conclusions This study extends the existing literature by shedding light on the interconnectedness of contextual factors within the ICF and various facets of perceived participation, including a sense of connection, efficacy and meaning. These findings provide valuable insights for stakeholders such as urban planners and policymakers in developing inclusive environments that enhance the overall quality of participation for people with multiple sclerosis and gait impairment. Patient or Public Contribution This study reports on the lived experiences of people with multiple sclerosis and gait impairment who (intend to) use mobility assistive devices. The research team stood in close exchange with project members of the German Multiple Sclerosis Society Lower Saxony, a group representing the interests of people with multiple sclerosis, to design and conduct the focus group interviews. The results from the focus group interviews were the basis for the design of a participatory future workshop in which people with multiple sclerosis and stakeholders involved in the healthcare process collaboratively developed recommendations for improving the provision of mobility assistive devices. Trial Registration German Clinical Trials Register number: DRKS00025532.